Fresno Merced Counties Legal Services Office Holiday Party - Watkins, Howard::::::::: (1982)
Potluck luncheon in library: Gloria Escalante, Christina Russell, ? And daughter, Jan Pearson, Mary Ludy, Virginia Salmeron, ?, Howard Watkins